2012
DOI: 10.1088/0957-4484/23/11/115606
|View full text |Cite
|
Sign up to set email alerts
|

Growth of InAs/InAsSb heterostructured nanowires

Abstract: We report the growth of InAs/InAs(1-x)Sb(x) single and double heterostructured nanowires by Au-assisted chemical beam epitaxy. The InAs(1-x)Sb(x) nanowire segments have been characterized in a wide range of antimony compositions. Significant lateral growth is observed at intermediate compositions (x ~ 0.5), and the nucleation and step-flow mechanism leading to this lateral growth has been identified and described. Additionally, CuPt ordering of the alloy has been observed with high resolution transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…The CuPt-type ordering is energetically stable in InAs 0.5 Sb 0.5 [51] and has been experimentally observed under various growth conditions [37][38][39][40][41]. We find that this structure also has the biggest enhancement of the SOS (see Supplementary Material [51]).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The CuPt-type ordering is energetically stable in InAs 0.5 Sb 0.5 [51] and has been experimentally observed under various growth conditions [37][38][39][40][41]. We find that this structure also has the biggest enhancement of the SOS (see Supplementary Material [51]).…”
mentioning
confidence: 52%
“…We also find that for the latter the spinorbit energy E SO [36] can be as large as 24 meV. Experimental evidence for the CuPt-ordering of InAs 0.5 Sb 0.5 exists [37][38][39][40][41], and we argue that nanowires of this structure can be grown with molecular beam epitaxy.The SOS of the conduction band in zincblende structures is at most cubic in k around the Γ-point [25]. In both III-V materials, the conduction band has a minimum at Γ and an s-like character dictated by T d symmetry.…”
mentioning
confidence: 62%
“…4 An alternative to forming InAs 1Àx Sb x layer-by-layer is to grow the material in the shape of nanowires, where epitaxial and dislocation-free materials with various As/Sb compositions can be formed on the same starting substrate. [5][6][7] Nanowires of binary InAs and InSb are currently studied very intensely in research related to quantum computation, motivated by the strong spin-orbit interaction in InAs and InSb, which simplifies spin manipulation, [8][9][10] and the observation of new quasiparticles, such as Majorana fermions. 11 Access to ternary InAs 1Àx Sb x material will likely offer a possibility to tune important material-related properties, such as spin-orbit coupling and quantum confinement.…”
mentioning
confidence: 99%
“…They suggested that under the same conditions, due to a decreased effective V/III ratio at the liquid solid interface, the incorporation of Sb in the NWs could be achieved to a significantly higher level than for planar epitaxy. Latter than the vapor phase epitaxy, InAs/InAs 1−x Sb x and their double heterostructures were successfully achieved via UHV CBE growth and the Sb content was increased to x = 0.94 [226] as shown in …”
Section: Reviewmentioning
confidence: 99%